Assessment of bone in Ehlers Danlos syndrome by ultrasound and densitometry. Issue 10 (1st October 1998) - Dolan, A L; Arden, N K; Grahame, R; Spector, T D
Abstract : OBJECTIVE: Ehlers Danlos syndrome (EDS) is an inherited disorder of connective tissue characterised by hyperextensible skin, joint laxity, and easy bruising. There are phenotypic similarities with osteogenesis imperfecta, but in EDS a tendency to fracture or altered bone mass has not previously been considered to be a cardinal feature. METHOD: This case-control design study investigates whether 23 patients with EDS had differences in fracture rates, bone mass, and calcaneal ultrasound parameters compared with age and sex matched controls. RESULTS: 23 cases of EDS (mean (SD) age 38.5 (15.5)) were compared with 23 controls (mean age 37.8 (14.5)). A significant reduction in bone density measured by dual energy x ray absorptiometry was found at the neck of femur by 0.9 SD, p = 0.05, and lumbar spine by 0.74 SD, p = 0.02. At the calcaneum, broad band ultrasound attenuation and speed of sound were significantly reduced compared with controls by 0.95 SD (p = 0.004) and 0.49 SD (p = 0.004) for broad band ultrasound attenuation and speed of sound respectively. Broad band ultrasound attenuation and speed of sound remained significantly reduced after adjusting for bone mineral density (BMD). After adjusting for functional status (HAQ), age and sex, hypermobility was inversely correlated with broad band ultrasound attenuation and SOS, but not BMD at hip or spine. Previous fracture was 10 times more common in EDS (p < 0.001), with 86.9% of patients reporting a total of 47 low impact fractures, compared with 8.7% of controls. CONCLUSION: This study has identified a tendency of EDS patients to fracture, have low bone mass and abnormal bone structure. The aetiology is likely to be multifactorial, with an inherited structural element, accentuated by immobility or reduced exercise. This is one of the first clinical studies to suggest ultrasound can detect structural differences in bone, independent of dual energy x ray absorptiometry.